1987
DOI: 10.1071/bi9870295
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Exogenous Growth Hormone on Milk Production and Nutrient Uptake by Muscle and Mammary Tissues of Dairy Cows in Mid-lactation

Abstract: Responses to exogenous growth hormone were measured in lactating dairy cows surgically prepared to allow measurement of nutrient exchanges across mammary and hind-limb muscle tissues. Cows were injected daily with either saline or growth hormone, at a dose of 0·1 mg/kg liveweight, over periods of 6 days.During administration of growth hormone milk yield, milk fat content and yields of milk fat protein and lactose increased. Arterial plasma concentrations of glucose and non-esterified fatty acids were increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
45
0
2

Year Published

1988
1988
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 19 publications
8
45
0
2
Order By: Relevance
“…In that study, milk lactose production represented a major use of lost glucose. McDowell et al (1987b) demonstrated that rbGH treatments reduced glucose uptake by the hindlimb muscle and increased glucose uptake by the mammary gland, lending further support that diabetogenesis is an inherent property ofthe rbGH molecule (Hart et al 1984). We additionally propose that IGF-I plays a fundamental role in the diabetogenic activities of rbGH.…”
Section: Effects Of Growth Hormone On Body Conditionmentioning
confidence: 79%
“…In that study, milk lactose production represented a major use of lost glucose. McDowell et al (1987b) demonstrated that rbGH treatments reduced glucose uptake by the hindlimb muscle and increased glucose uptake by the mammary gland, lending further support that diabetogenesis is an inherent property ofthe rbGH molecule (Hart et al 1984). We additionally propose that IGF-I plays a fundamental role in the diabetogenic activities of rbGH.…”
Section: Effects Of Growth Hormone On Body Conditionmentioning
confidence: 79%
“…1984) when administered over short periods of several days. In such short-term studies it has been shown 0004-9417/88/030357$03.00 that nutrient utilization in the body as a whole McDowell et al 1987b) and in muscle and mammary tissues (McDowell et al 1987a(McDowell et al , 1988 is altered by GH so as to increase the supply of nutrients for milk synthesis as was suggested originally by Bauman and Currie (1980) and Bines and Hart (1982).…”
Section: Introductionmentioning
confidence: 99%
“…Plasma glucose and NEFA, blood acetate, lactate and 3-hydroxybutyrate and plasma insulin and growth hormone were measured using the procedures outlined by McDowell et al (1987aMcDowell et al ( , 1988.…”
Section: Metabolites and Hormonesmentioning
confidence: 99%
“…It indicates that both cooled and noncooled cows were in positive energy balance. These findings would not affect the irreversible loss of glucose, which has been shown to increase in cows with negative energy balance (McDowell et al, 1987). The reversible turnover rate of [3-3 H] glucose represents the total glucose turnover rate as the 3 H is not recycled from products of partial glucose degradation (Katz et al, 1965).…”
Section: Discussionmentioning
confidence: 98%